2004
DOI: 10.1093/toxsci/kfh019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Responses of Mice, Rats, and Hamsters to Subchronic Inhalation of Ultrafine Titanium Dioxide Particles

Abstract: A multispecies, subchronic, inhalation study comparing pulmonary responses to ultrafine titanium dioxide (uf-TiO(2)) was performed. Female rats, mice, and hamsters were exposed to aerosol concentrations of 0.5, 2.0, or 10 mg/m(3) uf-TiO(2) particles for 6 h/day, 5 days/week, for 13 weeks. Following the exposure period, animals were held for recovery periods of 4, 13, 26, or 52 weeks (49 weeks for the uf-TiO(2)-exposed hamsters) and, at each time point, uf-TiO(2) burdens in the lung and lymph nodes and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
370
4
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(426 citation statements)
references
References 27 publications
31
370
4
13
Order By: Relevance
“…A research program to investigate inter-species differences as a result of exposure to TiO 2 and to conduct detailed epidemiological surveys of the major manufacturing sites was initiated by a consortium of TiO 2 manufacturers in Europe (under the European Chemistry Industry Council; CEFIC) and North America (under the American Chemistry Council; ACC). Some detailed results published from these studies showed distinct species differences in lung responses, particle distributions and clearance rates (Bermudez et al, 2002(Bermudez et al, , 2004.…”
Section: Introductionmentioning
confidence: 98%
“…A research program to investigate inter-species differences as a result of exposure to TiO 2 and to conduct detailed epidemiological surveys of the major manufacturing sites was initiated by a consortium of TiO 2 manufacturers in Europe (under the European Chemistry Industry Council; CEFIC) and North America (under the American Chemistry Council; ACC). Some detailed results published from these studies showed distinct species differences in lung responses, particle distributions and clearance rates (Bermudez et al, 2002(Bermudez et al, , 2004.…”
Section: Introductionmentioning
confidence: 98%
“…In mammalian models, routes of exposure examined include inhalation [7][8][9][10][11][12], oral administration (TiO 2 NPs) [13] and adsorption via the skin (microfine ZnO and TiO 2 ) [14]. Where toxicity has been demonstrated, a common finding has been the incidence of an inflammatory response [7,10,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…If the doses were expressed as surface area rather than mass in the experiment, the fact that the doseresponse relationship appeared as a straight line, led to the opinion that larger surface area is a factor in the strong inflammatory response to TiO 2 nanoparticles 7,27,30) . Bermudez et al 31,32) compared the results of a 13-week inhalation study of TiO 2 nanoparticles in rat, hamster and mouse with previous reports of TiO 2 microparticles. They reported, that at the same mass-based exposures, greater pulmonary inflammatory responses were seen in the groups exposed to TiO 2 nanoparticles than in the groups exposed to TiO 2 microparticles, and concluded that differences in surface area were the cause of this result.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%
“…One of the possible reasons for disagreement is that many studies have been performed using particles with different particle size, surface properties, impurities and crystal structures, involving complex interactions among many factors, and it has been difficult to separate the sole effects of particle size and surface area among many factors. For example, in the research of Bermudez et al 31,32) and Sager et al 35) the TiO 2 nano-and micro-particles used came from different sources and had different crystal structures. Both used the 80% anatase -20% rutile form of TiO 2 particles, generally known by the product name P25, made by Evonik as TiO 2 nanoparticles.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%